Out of the Shadows and into the Classroom: Immigrant Legalization, Hispanic Schooling and Hispanic Representation on School Boards - Navid Sabet (Center for Economic Studies and ifo Institute (CESifo), 2023)
I exploit the 1986 Immigration Reform and Control Act (IRCA), which legalized millions of Hispanic migrants in the USA, to study the impact of immigrant legalization on schooling outcomes. Although undocumented migrants are entitled to public education, I find significant post-legalization increases in student enrollment and student-to-teacher ratios in public schools with greater exposure to IRCA migrants. This effect is driven by increased Hispanic enrollment, while whites sort out of public education and into private schooling. The IRCA differentially increases Hispanic school board members and school expenditure, highlighting legal status as a driver of Hispanic human capital accumulation and representation.
Keywords: I21; J15; H52; 330; schooling; human capital; minority representation; legal status